2015
DOI: 10.1016/j.bbr.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of embryonic cyclosporine exposures on brain development and behavior

Abstract: Cyclosporine, a calcineurin inhibitor, is successfully used as an immunosuppressant in transplant medicine. However, the use of this pharmaceutical during pregnancy is concerning, since calcineurin is thought to play a role in neural development. The risk for human brain development is difficult to evaluate, because of a lack of basic information on the sensitive developmental times and the potentially pleiotropic effects on brain development and behavior. In the present study, we use zebrafish as a model syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
3
18
1
1
Order By: Relevance
“…The 24 h treatment of the 72 hpf larvae that have a functional liver was intended not only to generate quantifiable moderate toxic endpoints but also to explore whether there was any alteration in the specific drug‐metabolizing CYP enzyme. Exposure of 72 hpf larvae to 10 μ m CsA only has been shown to cause significant behavioral defects but no morphological anomalies (Clift et al, ). Consistent with this report, our current study showed that 10 μ m CsA‐treated larvae developed like control larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The 24 h treatment of the 72 hpf larvae that have a functional liver was intended not only to generate quantifiable moderate toxic endpoints but also to explore whether there was any alteration in the specific drug‐metabolizing CYP enzyme. Exposure of 72 hpf larvae to 10 μ m CsA only has been shown to cause significant behavioral defects but no morphological anomalies (Clift et al, ). Consistent with this report, our current study showed that 10 μ m CsA‐treated larvae developed like control larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Visual, motor and brain defects may have contributed to the pattern of impairments in the PCB-exposed larvae which included attenuated avoidance on the BD assay and elevated freezing and thigmotaxis on the BD/SD assay. One strategy that could prove useful in identifying the source of these functional deficits would be to vary the timing of the PCB-exposure window (Clift et al, 2015). Overall, these findings highlight the potential risks of PCB-exposure to human fetal and neonatal development and the importance of continued monitoring of PCB levels in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…[124][125][126][127][128] Use of corticosteroids in the first trimester of pregnancy is not advisable due to the possible increased risk of cleft palate, and ciclosporin use in pregnant women should be considered with extreme caution due to potential adverse embryotoxic and teratogenic effects. 78,129,130 Published evidence on the use of montelukast during pregnancy suggests that there is no increased risk of major malformations above the baseline rate in the general population; however, one study reported a significantly lower birth weight of babies whose mothers had been treated with montelukast. 131 Further clinical studies are required to be able to fully evaluate the efficacy and safety of montelukast in pregnant women.…”
Section: Pregnant and Lactating Womenmentioning
confidence: 99%